Perceptions of black employees regarding the psychological contract within an African context - Lutendo B. Mahadulula; Maggie Holtzhausen (SA Journal of Human Resource Management)
Orientation: There is a need for researchers to investigate the constructs of psychological contract, work engagement and turnover intention within the context of the African knowledge system (AKS).